The food retail revolution in poor countries: Is it coming or is it over? Evidence from Madagascar - Minten, Bart (International Food Policy Research Institute, 2007)
Global retail chains are becoming increasingly dominant in the global food trade and their rise leads to dramatic impacts on agricultural supply chains and on small producers. However, the prospects and impacts of a food retail revolution in poor countries are not yet well understood. Here, we examine this question in Madagascar, a poor but stable country where global retailers have been present for over a decade. Our survey and analysis finds that while global retail chains sell better quality food, their prices are 40 to 90% higher, ceteris paribus, than those seen in traditional retail markets. In poor settings, characterized by high food price elasticities, a lack of willingness to pay for quality, and small retail margins, supermarkets appear to set prices with an eye toward maximizing profits based on price-inelastic demands for quality products from a small middle class interested in one-stop shopping. It seems unlikely that global retail chains will further increase their food retail share in such poor settings.